Linux cookbook - Schroder, Carla (O'Reilly, 2004)
This unique and valuable collection of tips, tools, and scripts provides clear, concise, hands-on solutions that can be applied to the challenges facing anyone running a network of Linux servers from small networks to large data centers in the practical and popular problem-solution-discussion O'Reilly cookbook format.The Linux Cookbook covers everything you'd expect: backups, new users, and the like. But it also covers the non-obvious information that is often ignored in other books the time-sinks and headaches that are a real part of an administrator's job, such as: dealing with odd kinds of devices that Linux historically hasn't supported well, building multi-boot systems, and handling things like video and audio.The knowledge needed to install, deploy, and maintain Linux is not easily found, and no Linux distribution gets it just right. Scattered information can be found in a pile of man pages, texinfo files, and source code comments, but the best source of information is the experts themselves who built up a working knowledge of managing Linux systems. This cookbook's proven techniques distill years of hard-won experience into practical cut-and-paste solutions to everyday Linux dilemmas.Use just one recipe from this varied collection of real-world solutions, and the hours of tedious trial-and-error saved will more than pay for the cost of the book. But those who prefer to learn hands-on will find that this cookbook not only solves immediate problems quickly, it also cuts right to the chase pointing out potential pitfalls and illustrating tested practices that can be applied to a myriad of other situations.Whether you're responsible for a small Linux system, a huge corporate system, or a mixed Linux/Windows/MacOS network, you'll find valuable, to-the-point, practical recipes for dealing with Linux systems everyday. The Linux Cookbook is more than a time-saver; it's a sanity saver.